QUALITY IMPROVEMENT OF DISQUALIFIED TIGER PRAWN (Penaeus monodon Fab.) BROODSTOCK USING DOPAMINE - Etty Riani; MOZES TOELIHERE; ICHSAN EFFENDIE; TUTI L YUSUF; SRIHADI AGUNGPRIYONO (BIOTROPIA, 2010)
Disqualified  tiger prawn broodstock  is the one that has undergone ablation after two breeding periodes which causes high production cost pollution of environment  and difficulties in  providing it continuously  with enough quantity at exact time  The purpose of this  study is to find  the proper dosage of dopamine  which will give  good quality  for  breeding of the disqualified tiger prawn  because  dopamine  inhibits  maturation  so it has  enough  time for maturation  and can be improved  the eggs  quality This experiment used 15 pairs the twice breeding tiger prawn  which is taken from Perigi  Central Java  The sample were treated with  difference dosage of dopamine dosage  109    108  107  106  moll  and  controlinjected by aquabidest  The parameters  were identified  in this  experiment  are  duration  days  for eggs maturation fecundity fertilizing rate  hatching  rate   egg  diameter  and phototaxis respnnsive of the  nauplii The result of this research are the of the average  of duration  for eggs  maturation  on the broodstock  that were injected  dopamine dosage  109    108  107  106  moll  and  control were   14  12  4  2  5  days  Fecundity   561489   503000   384205   230850   and  150034   Fertilizing rate  898    821   560   463     and  232      Hatching rate   7953  7253   4775   1227   and  366   Diameter  029  029  029  027  and  027mm   The nauplii  that had  produced by  injected broodstock by dosage  109    108  107  have the positive phototaxis responsive  while dosage   106   and control  were weak Key words Disqualified  dopamine dosage duration maturation fecundity fertilizing hatching diameters nauplii